Analisis Teologis: "Total Depravity" dalam Konteks Teologi Kovenan dan Refleksinya terhadap Kehidupan Manusia - Daniel Pesah Purwonugroho; Yohanes Telaumbanua (KHAMISYIM: Jurnal Teologi dan Pendidikan Kristiani, 2024)
Total Depravity is the condition of human sinfulness resulting from the failure of Adam and Eve to respond to God's covenant of work in the Garden of Eden. Sin renders human consciousness incapable of choosing to accept salvation from God. The state of total depravity renders humans entirely unable to respond to the covenant between humanity and God. Covenant Theology begins with God taking the initiative to establish a covenant of work with Adam. Adam's failure results in death entering the lives of humanity. Jesus, the eternal Son of God, enters into a covenant with God the Father. Jesus and His faithfulness become the determining factor in the covenant between God and humanity. Through a descriptive qualitative approach, the author expounds on the condition of total depravity and how Jesus serves as the focal point of a superior covenant, along with its reflection in human life. Abstrak Total depravity adalah kondisi keberdosaan manusia akibat dari kegagalan Adam dan Hawa merespon perjanjian kerja Allah di taman Eden. Dosa membuat kesadaran manusia tidak mungkin membuat manusia dapat memilih untuk menerima anugerah keselamatan dari Allah. Dalam keadaan rusak total, mustahil bagi manusia untuk mengadakan perjanjian antara manusia dan Tuhan. Teologi perjanjian dimulai dengan Allah mengambil inisiatif untuk membuat kontrak yang sah dengan Adam. Adam gagal, kegagalan Adam membawa kematian pada kehidupan manusia. Yesus adalah Allah Anak yang berasal dari kekekalan yang mengikat perjanjian dengan Allah Bapa. Yesus dan kesetiaanNya menjadi penentu perjanjian antara Allah dengan manusia. Melalui pendekatan kualitatif deskriptif, penulis menguraikan tentang kondisi total depravity dan bagaimana Yesus menjadi titik tumpu perjanjian yang lebih baik serta refleksinya dalam kehidupan manusia. Kata Kunci : Total Depravity, Kovenan, Refleksi, Yesus